A modern day perspective on smoking in peripheral artery disease - Behrooz, Leili; Abumoawad, Abdelrhman; Rizvi, Syed Husain M.; Hamburg, Naomi M. (Frontiers in Cardiovascular Medicine, 2023)
Peripheral artery disease (PAD) is associated with increased risk of cardiovascular morbidity and mortality, poor functional status, and lower quality of life. Cigarette smoking is a major preventable risk factor for PAD and is strongly associated with a higher risk of disease progression, worse post-procedural outcomes, and increased healthcare utilization. The arterial narrowing due to atherosclerotic lesions in PAD leads to decreased perfusion to the limbs and can ultimately cause arterial obstruction and limb ischemia. Endothelial cell dysfunction, oxidative stress, inflammation, and arterial stiffness are among the key events during the development of atherogenesis. In this review, we discuss the benefits of smoking cessation among patients with PAD and the use of smoking cessation methods including pharmacological treatment. Given that smoking cessation interventions remain underutilized, we highlight the importance of incorporating smoking cessation treatments as part of the medical management of patients with PAD. Regulatory approaches to reduce the uptake of tobacco product use and support smoking cessation have the potential to reduce the burden of PAD.